FACTORS ASSOCIATED WITH MICROBIAL CONTAMINATION IN CATERING FOOD SERVICES IN PALEMBANG CITY, SOUTH SUMATRA - Yuniati, Faiza; Anggraini, Karina; Efriza; Rismarini (Perhimpunan Ahli Epidemiologi Indonesia, 2025)
Background: Food safety is a critical aspect of public health, particularly in catering services where food is prepared and distributed in bulk, increasing the risk of microbial contamination. Understanding the contributing factors to microbial contamination in such settings is essential for developing effective prevention strategies. This study aimed to determine factors associated with microbial contamination in catering food services within the Padang Selasa Health Center area of Palembang City. Methods: A quantitative cross-sectional design was employed, involving 50 food handlers and 20 food samples (rice and animal-based side dishes). Microbial counts were analyzed following the Indonesian National Standard (SNI 7388:2009). Independent variables included demographic characteristics (age, gender, education, work experience), knowledge, hygiene-sanitation behavior, and environmental factors (temperature and humidity). Results: Results revealed a mean microbial count of 11,632 colonies/25 grams, with significant negative correlations between microbial contamination and food handlers’ age, tenure, knowledge, and hygiene behavior (p < 0.05). Positive correlations were observed between microbial counts and storage temperature as well as food ingredient selection, while relative humidity showed a negative association. No significant relationships were found with gender or education level. Conclusion: These findings underscore the critical role of food handler experience, knowledge, sanitation behavior, and environmental controls in mitigating microbial contamination in catering food. The study recommends targeted, continuous training and stringent environmental management to enhance food safety and public health in community catering services.